2018
DOI: 10.18632/oncotarget.24480
|View full text |Cite
|
Sign up to set email alerts
|

Integrated DNA methylation analysis identifies topographical and tumoral biomarkers in pilocytic astrocytomas

Abstract: Pilocytic astrocytoma (PA) is the most common glioma in pediatric patients and occurs in different locations. Chromosomal alterations are mostly located at chromosome 7q34 comprising the BRAF oncogene with consequent activation of the mitogen-activated protein kinase pathway. Although genetic and epigenetic alterations characterizing PA from different localizations have been reported, the role of epigenetic alterations in PA development is still not clear. The aim of this study was to investigate whether disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…These results confirmed the association between promoter hypermethylation and gene downregulation already reported, considering methylation as a mechanism for gene transcriptional inactivation in cancer [34,35]. Moreover, the expression levels of most of the genes studied in this work, were already low in colon normal tissues (GTEx data, https://www.gtexportal.org) supporting the idea that methylation in cancer targets genes barely expressed in tissues where tumour arises [4,[36][37][38]. Interestingly, our study shows that these genes are further repressed in tumour tissues that can be observed only by means of a targeted gene expression analysis as previously reported [4,36,39].…”
Section: Discussionsupporting
confidence: 91%
“…These results confirmed the association between promoter hypermethylation and gene downregulation already reported, considering methylation as a mechanism for gene transcriptional inactivation in cancer [34,35]. Moreover, the expression levels of most of the genes studied in this work, were already low in colon normal tissues (GTEx data, https://www.gtexportal.org) supporting the idea that methylation in cancer targets genes barely expressed in tissues where tumour arises [4,[36][37][38]. Interestingly, our study shows that these genes are further repressed in tumour tissues that can be observed only by means of a targeted gene expression analysis as previously reported [4,36,39].…”
Section: Discussionsupporting
confidence: 91%
“…returning to the conditions required during development. However, it should also be considered the possibility that the methylation status found in the tumour actually mirrors the cell of origin pattern clonally expanded [24, 40, 4648]. In this case, it may not represent a cause or an effect of tumorigenesis, but still a cancer-specific clustered PCDH methylation pattern would remain a valuable biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The number of probes mapping in PCDHG @ cluster in the different BeadChips are reported in Additional file 1: Figure S1. Further information and clinical data are available in Antonelli et al (PA study) and Fadda et al (CRC study) [24, 25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the consistency of spatio-temporal localization of even this small set of genes across multiple datasets partially mitigates this limitation. Moreover, several PA-DR genes, most notably Pax3 and the members of the Iroquois family (Irx5 and Irx2), have consistently been reported to be differentially methylated [25,51,52] and expressed at both the mRNA [25,45,51,53] and protein levels [53] in infratentorial tumors, strengthening the selection of genes used in this study.…”
Section: Plos Onementioning
confidence: 52%